Evaluation of the energetic and environmental potential of the hydrothermal carbonization of biowaste: Modeling of the entire process chain - Stobernack, Niklas; Mayer, Felix; Malek, Christian; Bhandari, Ramchandra (Bioresource technology, 2020)
•Biowaste was treated hydrothermally under different reaction intensities.•A statistical model was calibrated to predict mass and element distribution.•An industrial-scaled hydrothermal carbonization (HTC) plant was modelled.•Energy and mass distributions along the process chain were holistically calculated.•The global warming potential for electricity production from HTC-char was computed. This study outlines the entire process chain related to an industrial-sized hydrothermal carbonization (HTC) plant, which treats the organic fraction of municipal solid waste. A parameter study, carried out in laboratory-scaled experiments, was used to create a model starting with the substrate preparation and ending with the production of electricity. It was designed to be infinitely variable with respect to different reaction intensities within certain boundary conditions. Contrary to previous research endeavors, all components related to the HTC process and modules for the post-treatment of co-products including heat recovery and process water treatment were integrated. Based on this model, the claim that HTC-char is a more environmentally friendly energy carrier than lignite was investigated. In the realm of a life cycle assessment, a GWP of 0.45–0.70 kg CO2,Eq/kWhel was revealed for the electricity production from HTC-char. It, thus, outcompetes the electricity production from lignite (1.05–1.40 kg CO2,Eq/kWhel).